Genre study in result and discussion section of scientific papers - Salma, Arina Mawahibi; Salsabila, Karenina Dwi; Sholikhah, Lianatus; Fadillah, Delfi Frizka; Kurniawan, Agung Budi (Universitas Negeri Medan, 2025)
This study examines the application of genre patterns in the